Durability of carbon dioxide removal is critical for Paris climate goals - Cyril Brunner; Zeke Hausfather; Reto Knutti (Communications Earth & Environment)
Abstract Carbon Dioxide Removal is essential for achieving net zero emissions, as it is required to neutralize any residual CO2 emissions. The scientifically recognized definition of Carbon Dioxide Removal requires removed atmospheric CO2 to be stored “durably”; however, it remains unclear what is meant by durably, and interpretations have varied from decades to millennia. Using a reduced-complexity climate model, here we examined the effect of Carbon Dioxide Removal with varying CO2 storage durations. We found that storage duration substantially affects whether net zero emissions achieve the desired temperature outcomes. With a typical 100-year storage duration, net zero CO2 emissions with 6 GtCO2 per year residual emissions result in an additional warming of 0.8 °C by 2500 compared to permanent storage, thus putting the internationally agreed temperature limits at risk. Our findings suggest that a CO2 storage period of less than 1000 years is insufficient for neutralizing remaining fossil CO2 emissions under net zero emissions. These results reinforce the principle that credible neutralization claims using Carbon Dioxide Removal in a net zero framework require balancing emissions with removals of similar atmospheric residence time and storage reservoir, e.g., geological or biogenic.